Identifying Grammarly Automated Writing Evaluation and Self-Editing by Administrative Officer - Rizky Eka Prasetya; Didik Hariyadi Raharjo; Sofiani, Fenti (JELLT (Journal of English Language and Language Teaching), 2024)
Automated writing evaluation (AWE) tools have been extensively used in foreign language writing classrooms, and their use has been progressively expanding recently. The study investigates an overview of Grammarly’s Automated Writing Evaluation (AWE). The research employed a quasi-experimental, comparative design with convenience sampling to assess the effects of Grammarly on the automated writing evaluation and self-editing of 56 administrative officers. The findings demonstrate that Grammarly’s AWE editing groups produced many better-written outputs. Grammarly’s AWE editing and self-editing experimental groups outperformed the control groups that did not engage in Grammarly’s AWE software. The level and complexity of the impact articles written by experimental groups are much more significant. The comparison was made between automated and non-automated editing. It demonstrates the existence of a considerable advantage for AWE editing. There were statistically significant changes in favor of the post-test between the pretest and post-test mean scores for both groups. These outcomes may be clarified with the software’s contribution. There is no difference between the experimental groups that are statistically significant. This result corresponds with whether there is a substantial difference in the effects on the writings of Grammarly’s AWE and self-editing experimental groups.